2016
DOI: 10.1111/his.12948
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of senescence markers p14ARF and p16INK4a in breast cancer is associated with an increased risk of disease recurrence and poor survival outcome

Abstract: These finding suggest p16(INK4a) expression and p14(ARF) expression may play an important role in the progression of proliferative breast tissue to invasive cancer, and may be useful as prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…The gene encoding p16 is mutated or downregulated in several cancer cells. Breast carcinoma progression has been related to overexpression of p16 [14], and this has been reported in head and neck squamous carcinoma [15], in prostate carcinoma [16], and also in aggressive subtypes of bladder carcinoma [17][18][19][20].…”
Section: Discussionmentioning
confidence: 93%
“…The gene encoding p16 is mutated or downregulated in several cancer cells. Breast carcinoma progression has been related to overexpression of p16 [14], and this has been reported in head and neck squamous carcinoma [15], in prostate carcinoma [16], and also in aggressive subtypes of bladder carcinoma [17][18][19][20].…”
Section: Discussionmentioning
confidence: 93%
“…About 39% of the invasive breast carcinoma of ductal type showed p16 overexpression (moderate and intense expression) in a previous study in which 1042 histological samples obtained from primary site were analyzed with a similar score used in present study [9]. In this previous study, the authors also concluded that patients with strongly p16-positive cancers had a 2.5-fold increased risk of death and more than three-fold increased risk of disease recurrence as compared with those with p16-negative cancers.…”
Section: Discussionmentioning
confidence: 97%
“…The immunoreactivity of anti-p16 antibody was evaluated and compared with the expression of claudin-4 and MOC-31 by using total immunostaining score (TIS), which is the product of the proportion score and the intensity score. This score has been previously used to evaluate the expression of p16 and EpCAM in histological specimens [9,14,15]. Here, this score was applied to enable comparison between p16 expression with those of MOC-31 (anti-EpCAM clone) and claudin-4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the relationship between the expression level of three tumor suppressors P16, P14, and p15 in breast cancer patients. Most of these case‐control studies have shown that elevated P16 expression was associated with increased mammary cell proliferation and this progresses to breast cancer, while there are some studies that showed an association with the down‐regulated expression level of this tumor suppressor gene in breast cancer tissues (Meseure et al, ; Pare, Shin, & Lee, ; Todd, Langan, & Sclafani, ; Yang et al, ). It should be noted that elevated p16 gene expression was observed in Rb‐negative tumors, such as basal‐like breast cancers because inactivation of Rb results in up‐regulation of p16 expression in order to limit Cdk4 activity by a negative feedback mechanism.…”
Section: Anrilmentioning
confidence: 99%